“Impregnación en semillas de arroz con imidacloprid, pirimifos metílico y clorpirifos para controlar insectos en almácigo en Tarapoto” - Rios Vargas, Iris (2001)
The work research was present carried out in order to impregnating the insecticides: lmidacloprid, Methylic Pirimifos, Clorpirifos in seeds of rice to determine the lethal effect in insects to the Seedling level and its residual power up to 25 days after the transplant. lt was located in the 1 found "El Llano" of property of M. S. Alexandria'S, in the kilometer 13,5 of the highway Tarapoto -Moyobamba, compression of Cacatache of the district, of San Martín of the province and Country, inside the south latitude of 6º 32', Longitude west 76º23 • and altitude 350 m. s. n. m. The design of blocks complete randomized was used with 7 treatments (lmidacloprip to the doses of 1.20, 1.79, 2.40, 2.99 g, Pirimifos Methyl to 0.067 g, Clorpirifos to 0.096 g. of p. c. for Kg of seed of rice and a witness without insecticide) and with 3 repetitions. Ali the rehearsed insecticides didn't affect the germination neither to the vigor of the seed of the rice, improving their power to germinate among 0.33 to 2.03% with regard to the seed without treatment. Different levels of pollute of Tagosodes oryzicolus, Hidre/lia sp. and Lissorhoptrus sp. existed in each treatment. The lmidacloprid to the dose of 2.40 and 2.99 g of p. c., I Kg of seed rice, exercised the best control to Lissorhoptrus and Hidrellia until the 28 days in seedling and after the transplant up to 7 days. The Pirimifos methyl to the dose 0.067 g of p.c. I Kg of seed of rice, is accentuated starting from the 14 until the 28 days. The imidacloprid to the dose of 1. 79, 2.40, 2.99 g of p.c. / Seed Kg exercised the best control up to 21 days after the transplant of the rice. The residual power of lmidacloprid in their doses of commercial product that varied from 1.20 to 2.99 g, Pirimifos Methyl to 0.067 g. and the Clorpirifos to 0.096 g for Kg of seed of rice was 53 days.